Clinical evaluation of enzyme immunoassay in rapid diagnosis of herpes simplex infections. Issue 2 (February 1992) - Sillis, M
Abstract : AIMS: To evaluate the performance of antigen detection by IDEIA (NovoNordisk Ltd) in the rapid diagnosis of potentially serious herpes simplex (HSV) infections. METHODS: Nine hundred and twelve specimens from a variety of clinical sites, including ocular, mucocutaneous, respiratory and genital material, urines and necropsy tissue, were compared by enzyme immunoassay (EIA) and conventional culture for the presence of HSV. RESULTS: The EIA performed to a high level of sensitivity and specificity using a variety of specimen types. Some problems were encountered using cervical swabs from pregnant women and necropsy brain tissue. Analysis of clinical and contact history data of most patients giving discrepant results supported the evidence of recent HSV infection obtained by EIA. The mean culture time was 2.4 days (range one to eight days). CONCLUSIONS: The HSV EIA test performed to a high level of sensitivity (93.7%) and specificity (96.6%) when compared with culture using a variety of clinical material. These results assumed cell culture was 100% sensitive and specific. The actual performance of the EIA test is probably much higher. This approach to rapid HSV diagnosis should be used more widely, particularly in potentially serious cases.